Revitalisasi Sistem Bawon sebagai Strategi Pemberdayaan Tenaga Kerja Lokal dalam Perspektif Ekonomi Syariah: Studi Kasus di Dukuh Kemuning, Desa Semampir - Aan, Dwi Kuswianto (Journal of Principles Management and Business, 2025)
This study investigates the revitalization of the bawon tradition as a strategic effort to empower local labor within the framework of Islamic economics, focusing on Dukuh Kemuning, Semampir Village, Banjarnegara Regency, Central Java, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis to explore the socio-economic significance of bawon and its alignment with Islamic economic values. The bawon system, which reflects local wisdom rooted in mutual cooperation (gotong royong), social justice, and communal solidarity, demonstrates potential as a sustainable labor empowerment model consistent with sharia principles. The findings reveal that revitalizing bawon contributes to strengthening local economic resilience by integrating cultural practices with Islamic microfinance initiatives. The study concludes that an inclusive and adaptive empowerment model is essential one that harmonizes Islamic economic values with cultural heritage to respond effectively to contemporary socio-economic challenges.